KARAKTERISTIK DAN FUNGSI BAHASA DALAM JUAL BELI ONLINE PADA MEDIA WHATSAPP - Maulidawati (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
E-commerce has several different processes compare to offline stores. For example, the use of language as the most notable differences. This study examines the characteristics and functions of language in e-commerce on WhatsApp media. This study uses descriptive qualitative method. It is considered descriptive because it aims to describe linguistic phenomena which occur in certain community groups. Data collection in this study was carried out for one month starting from October 1 until October 31, 2021. The procedure of data collection is started with the listening method, then continued to the note-taking. The results of the study indicate that the use of language in e-commerce on WhatsApp has special characteristics and certain functions. The language features found in this study are code mixing, abbreviations, familiar greetings, and special terms. The language functions found in this study are personal functions, regulatory functions, interactional functions, heuristic functions, imaginative functions, instrumental functions, and representation functions.